Immunological Criteria of Autoaggression of Bronchial Asthma: Markers for Prediction of the Course and Selection of Adequate Pharmacotherapy - Nevzhoda, Anatoly; Nevzhoda, Olexandr (SSP Modern Pharmacy and Medicine, 2023)
About 10% of the population of highly developed European countries suffer from bronchial asthma. Monitoring for the period 2014-2021 regarding the number of patients with bronchial asthma in the Lviv region showed an increase in dynamics. The prevalence of bronchial asthma among the population is much higher, because patients do not always consult an allergist, but are treated by other specialists. This is a serious problem today, as blood pressure reduces the quality of life and work capacity of patients. Against the background of the increasing incidence of bronchial asthma, the frequency of the severe course of this disease is also increasing, which takes on the character of autoaggression and requires the use of increasing doses of glucocorticoids during treatment, up to daily replacement therapy. Accordingly, it is important to establish the immunological criteria of autoaggression in blood pressureas markers for predicting the severity of the course and choosing an adequate drug treatment.